(untitled) (International Journal of Engineering and Computer Science, 2017)
Sensors are electronic devices that are meant for recording particular environment variable for example temperature, pressure, speed etc. with the advancement in the field of electronics and sensors, it is possible to the gather physically measured data from sensors remotely. This is possible only because of the network facilities like Ethernet, Wi-Fi, and cellular networks that enable remote access to the data sampled by a sensor.Faults, errors, failures and attacks are common in a wireless communication and this imperfection in wireless communication compromises the effective data collection of a wireless sensing system. In this paper we are going to discuss some various challenges and solutions in robust data collection in wireless sensing system.